A new species of Didogobius (Teleostei: Gobiidae) from the Canary Islands - van Tassell, James L.; Kramer, Annemarie (Zootaxa, 2014)
Didogobius helenae is described from the Canary Islands. It has a sensory papillae pattern that is consistent with the current diagnosis for Didogobius, but lacks all head canals and pores that are present in other members of the genus. Pores, in general, are replaced by large papillae.  The species is defined by first dorsal fin VI; second dorsal fin I,10; anal fin I,9; pectoral fin 16–17; pelvic fin I,5 and disk shaped; lateral scales 28–30, cycloid at anterior, becoming ctenoid posteriorly; cycloid scales present on belly and posterior breast; predorsal region, cheek, operculum and base of pectoral fin without scales; lower most scale on the caudal fin-base with elongate, thickened ctenii along the upper and lower posterior edges. Color in life consists of four mottled, wide brown-orange bars separated by narrower white bars on the trunk, the cheek whitish with 5 more or less circular blotches of orange, outlined in dark brown and a black spot on ventral operculum. A key to the species is provided.